The Impact of Digital Marketing, Word-of-Mouth Promotion, and Service Quality on Customer Satisfaction - Cinta Laura; Nur Wahyunianti Dahri; Junaeda Junaeda; Muhammad Aqil; Tamin Tamin (Advances: Jurnal Ekonomi & Bisnis, 2026)
Purpose: This study examines the partial and simultaneous effects of digital marketing, word of mouth, and service quality on customer satisfaction at Toko ATK Damai in Topoyo District. Research Method: A quantitative associative design was employed using primary data collected from 95 customers selected through incidental sampling. Data were obtained through questionnaires, observation, interviews, and documentation. The hypotheses were tested using validity and reliability tests, multiple linear regression, t-tests, an F-test, and the coefficient of determination. Results and Discussion: Digital marketing positively and significantly affects customer satisfaction (t = 3.297; p = 0.001), as does word of mouth (t = 3.037; p = 0.003). Service quality has the strongest positive effect (t = 9.142; p < 0.001). Simultaneously, the three variables significantly influence customer satisfaction (F = 146.618; p < 0.001), explaining 82.9% of its variation. Implications: Retail managers should strengthen digital communication, encourage positive customer recommendations, and improve employee responsiveness and service consistency. Future studies should examine customer loyalty, trust, and repurchase intention across broader locations. Originality: This study integrates digital marketing, word of mouth, and service quality within a single model to explain customer satisfaction in a local general-merchandise retail context.